Gas barrier laminate, packaging film, packaging container, and packaging product

By using a thermoplastic resin base layer, an evaporated layer and a water-soluble polymer coating layer in the gas barrier laminate, combined with an anchor coating, the problem of insufficient lamination strength between the gas barrier and sealing layers after high-temperature cooking is solved. Excellent gas barrier and adhesion are achieved, reducing interlayer peeling and extending the shelf life of the packaging.

CN119300977APending Publication Date: 2025-01-10TOPPAN HOLDINGS INC
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202380044385.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-15
Filing Date
2023-06-13
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

There is room for improvement in the conventional gas barrier laminate after high-temperature cooking treatment and the lamination strength between the gas barrier and the sealing layer, and the problem of peeling between the sealing layer and the coating layer is prone to occur.

Method used

The substrate layer, vapor deposition layer and gas barrier coating layer containing thermoplastic resin were used to analyze the ratio (Si/C) of silicon atoms to carbon atoms (Si/C) from 0.25 to 0.90 by X-ray photoelectron spectroscopy, and in the narrow spectrum of Si2p orbital. The half-value width of the peak in the binding energy region of 100 to 107 eV is less than 1.85 eV, and the anchor coating is added to improve adhesion, and a composition containing a water-soluble polymer and a silicon compound is used as the coating material.

Benefits of technology

Even after high-temperature cooking, the gas-barrier laminate maintains excellent gas-barrier properties and has excellent adhesion with the sealing layer, reducing the phenomenon of interlayer peeling and extending the shelf life of the packaging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119300977A_ABST
    Figure CN119300977A_ABST
Patent Text Reader

Abstract

A gas barrier laminate provided with a substrate layer containing a thermoplastic resin, a vapor deposition layer, and a gas barrier coating layer in this order. When the surface of the gas barrier coating layer is subjected to elemental quantitative analysis by X-ray photoelectron spectroscopy, the ratio of silicon atoms to carbon atoms (Si / C) is 0.25-0.90, and the half width of the peak appearing in the binding energy region of 100-107 eV in the narrow spectrum of the Si2p orbital is 1.85 eV or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a gas barrier laminate, a packaging film, a packaging container, and a packaging product. Background Art

[0002] In order to suppress the deterioration and corruption of the contents and maintain their functions and properties, packaging bags and other packaging containers used for packaging food, medicines, etc. are required to have gas barrier properties that prevent water vapor, oxygen, and other gases that deteriorate the contents from entering. Therefore, gas barrier laminates have been used in these packaging bags.

[0003] The gas barrier laminate generally includes a substrate layer, a vapor-deposited layer, and a gas barrier coating layer in this order.

[0004] For example, the following patent document 1 discloses a gas barrier laminate, which comprises a substrate layer containing polyolefin, a metal oxide layer and a gas barrier coating layer in sequence, and has excellent gas barrier properties after retort sterilization or abuse test by making the content ratio a / b of the silicon atom content (a parts by mass) of the silane alkoxy compound or its hydrolysate to the water-soluble polymer content (b parts by mass) in the gas barrier coating layer be 3 / 97 or more and 45 / 55 or less in terms of mass ratio.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: International Publication No. 2021 / 220977 Summary of the invention

[0008] Problems to be solved by the invention

[0009] However, when a packaging bag is manufactured using a gas barrier laminate, a sealant layer is generally attached to the gas barrier coating layer. In addition, such packaging bags are sometimes sterilized at a high temperature of 121°C or above (hereinafter referred to as "high retort treatment") after being filled with contents and sealed.

[0010] However, the gas barrier laminate described in Patent Document 1 has room for improvement in terms of gas barrier properties after high-temperature retorting and lamination strength with a sealant layer.

[0011] The present disclosure has been made in view of the above problems, and an object of the present disclosure is to provide a gas barrier laminate, a packaging film, a packaging container, and a packaging product having excellent gas barrier properties even after high-temperature retorting and excellent adhesion with a sealant layer.

[0012] Means for solving problems

[0013] In order to solve the above-mentioned problems, the present disclosure provides a gas barrier laminate, which comprises a substrate layer including a thermoplastic resin, a vapor-deposited layer and a gas barrier coating layer in sequence, wherein on the surface of the gas barrier coating layer, when elemental quantitative analysis is performed on the surface of the gas barrier coating layer using X-ray photoelectron spectroscopy, the ratio of silicon atoms to carbon atoms (Si / C) is 0.25 to 0.90, and the half-value width of the peak appearing in the binding energy region of 100 to 107 eV in the narrow spectrum of the Si2p orbital is less than 1.85 eV.

[0014] The gas barrier laminate of the present disclosure has excellent gas barrier properties even after high-temperature retort treatment, and has excellent adhesion with the sealant layer.

[0015] In the gas barrier laminate, the thermoplastic resin may be polypropylene.

[0016] When the thermoplastic resin contained in the substrate layer is polypropylene, the gas barrier properties of the gas barrier laminate and the adhesion between the gas barrier laminate and the sealing layer tend to be easily reduced after high-temperature cooking treatment. However, the gas barrier laminate disclosed in the present invention has excellent gas barrier properties even after high-temperature cooking treatment and has excellent adhesion between the gas barrier laminate and the sealing layer.

[0017] The gas barrier laminate preferably further includes an anchor coating layer between the substrate layer and the vapor-deposited layer.

[0018] In this case, the surface smoothness of the anchor coating layer is higher than the surface smoothness of the substrate layer. Therefore, the thickness of the deposited layer can be made uniform, and the gas barrier properties of the gas barrier laminate can be further improved.

[0019] In the above-mentioned gas barrier laminate, the above-mentioned gas barrier coating layer can be composed of a solidified body of a composition containing a water-soluble polymer, a first silicon compound and a second silicon compound, wherein the above-mentioned first silicon compound contains at least one of a silaneoxy compound represented by the following general formula (1) and its hydrolysis product, and the above-mentioned second silicon compound contains at least one of a silaneoxy compound represented by the following general formula (2) and its hydrolysis product.

[0020] Si(OR 1 )4······(1)

[0021] (In the above general formula (1), OR 1 represents a hydrolyzable group. )

[0022] (R 2 Si(OR 3 )3) n ······(2)

[0023] (In the above general formula (2), R 2Represents a monovalent organic group, OR 3 represents a hydrolyzable group. n represents an integer greater than 1.)

[0024] In this case, the adhesion between the gas barrier coating layer and the vapor-deposited layer can be improved, and interlayer delamination in the gas barrier laminate can be suppressed.

[0025] In the gas barrier laminate, the gas barrier coating layer preferably has a thickness of 100 nm to 700 nm.

[0026] In this case, the gas barrier properties can be further improved even after the gas barrier layer is subjected to a high-temperature retort treatment, compared to a case where the thickness of the gas barrier coating layer is less than 100 nm. In addition, the gas barrier layer is less likely to curl than a case where the thickness of the gas barrier coating layer exceeds 700 nm, and can be easily used as a gas barrier layer for a packaging film contained in a packaging bag.

[0027] In the gas barrier laminate, the water-soluble polymer of the gas barrier coating layer may be a polyvinyl alcohol resin or a modified product thereof.

[0028] In this case, the composition can impart more excellent gas barrier properties to the gas barrier laminate by curing. In addition, even after curing, the composition can impart more excellent flexibility to the gas barrier laminate, and can further improve the gas barrier properties after abuse.

[0029] In the gas barrier laminate, the deposited layer may contain at least one selected from aluminum oxide and silicon oxide.

[0030] In this case, due to the SiO x and AlO x Both have excellent water vapor barrier properties, and thus can improve the water vapor barrier properties of the gas barrier laminate.

[0031] The present disclosure also provides a packaging film comprising the gas barrier layered product and a sealant layer.

[0032] Since the packaging film includes the gas barrier laminate, it has excellent gas barrier properties even after high-temperature retorting, and can suppress peeling between the sealant layer and the gas barrier coating layer in the gas barrier laminate constituting the packaging film.

[0033] Furthermore, the present disclosure provides a packaging container including the above-mentioned packaging film.

[0034] Since the packaging container includes the packaging film, it has excellent gas barrier properties even after high-temperature retorting, and can suppress delamination between the sealant layer and the gas barrier coating layer in the gas barrier laminate constituting the packaging film.

[0035] Furthermore, the present disclosure is a packaging product comprising the packaging container and a content filled in the packaging container.

[0036] The packaging product comprises the above-mentioned packaging container, which has excellent gas barrier properties even after high-temperature boiling treatment, and in the packaging film, the peeling between the gas barrier coating layer and the sealing layer contained in the gas barrier laminate can be suppressed, thereby suppressing the reduction in the quality of the contents caused by the mixing of oxygen for a long time.

[0037] Effects of the Invention

[0038] According to the present disclosure, there are provided a gas barrier laminate, a packaging film, a packaging container, and a packaging product which have excellent gas barrier properties even after high-temperature retort treatment and excellent adhesion with a sealant layer. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] [ Figure 1 ] is a cross-sectional view showing one embodiment of the gas barrier laminate disclosed in the present invention.

[0040] [ Figure 2 ] is a cross-sectional view showing an embodiment of the packaging film of the present disclosure.

[0041] [ Figure 3 ] is a side view showing an embodiment of the packaging product of the present invention. DETAILED DESCRIPTION

[0042] Hereinafter, embodiments of the present disclosure will be described in detail.

[0043] <Gas Barrier Laminate>

[0044] First, refer to Figure 1 One embodiment of the gas barrier laminate of the present disclosure will be described. Figure 1 This is a cross-sectional view showing one embodiment of the gas barrier laminate of the present disclosure. Figure 1 The gas barrier laminate 10 shown in the figure has, in order: a base layer 1 containing a thermoplastic resin, a vapor-deposited layer 3, and a gas barrier coating layer 4. On the surface of the gas barrier coating layer 4, the ratio of silicon atoms to carbon atoms (Si / C) measured by X-ray photoelectron spectroscopy (XPS) is 0.25 to 0.90, and the half-value width of the peak appearing in the binding energy region of 100 to 107 eV in the narrow spectrum of the Si2p orbital (hereinafter referred to as "the peak half-value width of the Si2p orbital") is 1.85 eV or less. It should be noted that the gas barrier laminate 10 may also have an anchor coating 2 as an intermediate layer between the base layer 1 and the vapor-deposited layer 3.

[0045] The gas barrier laminate 10 has excellent gas barrier properties even after high-temperature retorting, and has excellent adhesion between the gas barrier coating layer 4 and the sealant layer.

[0046] The base material layer 1 , the anchor coating layer 2 , the vapor-deposited layer 3 , and the gas barrier coating layer 4 are described in detail below.

[0047] (Base material layer)

[0048] The base material layer 1 is a layer that serves as a support for the gas barrier coating layer 4, and contains a thermoplastic resin. Examples of the thermoplastic resin include polyolefin resins, polyester resins, polyamide resins, polyether resins, acrylic resins, and natural polymer compounds (cellulose acetate, etc.). These may be formed alone or as a mixture of two or more.

[0049] Among them, as the thermoplastic resin, polyolefin resin or polyester resin is preferred from the viewpoint of heat resistance.

[0050] Examples of the polyolefin resin include polyethylene and polypropylene. From the viewpoint of retort resistance, polypropylene is preferred.

[0051] When the polyolefin resin as the thermoplastic resin contained in the base layer 1 is polypropylene, generally speaking, the gas barrier properties of the gas barrier laminate 10 and the adhesion to the sealant layer tend to be easily reduced after high-temperature cooking treatment, but the gas barrier laminate 10 has excellent gas barrier properties and excellent adhesion to the sealant layer even after high-temperature cooking treatment. Here, the polypropylene may be homopolypropylene or a propylene copolymer.

[0052] Examples of the polyester resin include polyethylene terephthalate (PET) and polyethylene naphthalate (PEN).

[0053] The substrate layer 1 may be a stretched film or a non-stretched film, but is preferably a stretched film from the viewpoint of gas barrier properties. Here, as the stretched film, a uniaxially stretched film and a biaxially stretched film can be listed, but is preferably a biaxially stretched film from the viewpoint of improving heat resistance.

[0054] There is no particular limitation on the thickness of the substrate layer 1, and for example, it may be 0.1 mm or less. The thickness of the substrate layer 1 may be 40 μm or less, 35 μm or less, or 30 μm or less. When the thickness of the substrate layer 1 is 40 μm or less, the flexibility of the gas barrier laminate 10 is further improved compared to the case where the thickness of the substrate layer 1 exceeds 40 μm, and the oxygen barrier property of the gas barrier laminate 10 after abuse can be further improved. However, from the viewpoint of improving strength, the thickness of the substrate layer 1 is preferably 10 μm or more, and more preferably 12 μm or more.

[0055] The base material layer 1 may contain additives such as an antistatic agent, an ultraviolet absorber, a plasticizer, and a lubricant as necessary.

[0056] (Middle layer)

[0057] The anchor coating layer 2 as an intermediate layer is a layer for further improving the adhesion between the base material layer 1 and the vapor-deposited layer 3 , and is provided between the base material layer 1 and the vapor-deposited layer 3 .

[0058] The material constituting the anchor coating 2 is not particularly limited as long as it can improve the adhesion between the substrate layer 1 and the vapor-deposited layer 3. Such materials include the reaction products of organic silane or organic metal compounds, polyol compounds, and isocyanate compounds. That is, the anchor coating 2 can also be called a carbamate adhesive layer. The organic silane is, for example, a trifunctional organic silane or a hydrolysis product of a trifunctional organic silane. The organic metal compound is, for example, a metal alkoxide or a hydrolysis product of a metal alkoxide. The metal elements contained in the organic metal compound are, for example, Al, Ti, Zr, etc. The hydrolysis product of the organic silane and the hydrolysis product of the metal alkoxide each have at least one hydroxyl group. From the viewpoint of transparency, the polyol compound is preferably an acrylic polyol. The isocyanate compound mainly functions as a crosslinking agent or a curing agent. The polyol compound and the isocyanate compound can be a monomer or a polymer.

[0059] The thickness of the anchor coating 2 is not particularly limited as long as it can improve the adhesion between the substrate layer 1 and the vapor-deposited layer 3, and is preferably 30 nm or more. In this case, compared with the case where the thickness of the anchor coating 2 is less than 30 nm, the smoothness of the surface of the anchor coating 2 can be further improved compared to the surface of the substrate layer 1, the thickness of the vapor-deposited layer 3 can be made more uniform, and the gas barrier properties can also be further improved. Therefore, the gas barrier properties of the gas barrier laminate 10 can be further improved. The thickness of the anchor coating 2 is more preferably 40 nm or more, and more preferably 50 nm or more. By increasing the thickness of the anchor coating 2, the reduction in water vapor barrier properties when external forces such as stretching are applied can be further suppressed. The thickness of the anchor coating 2 is preferably 300 nm or less. In this case, compared with the case where the thickness of the anchor coating 2 is 300 nm or more, the softness of the gas barrier laminate 10 is further improved, and the oxygen barrier properties of the gas barrier laminate 10 after abuse can be further improved. The thickness of the anchor coating 2 is more preferably 200 nm or less.

[0060] The intermediate layer may be a layer modified by subjecting the surface layer of the base layer 1 to a surface treatment such as corona treatment or plasma treatment, instead of the anchor coating layer 2. As the plasma treatment, reactive ion etching (RIE) may be used.

[0061] (Evaporated layer)

[0062] The vapor-deposited layer 3 is a layer formed by vapor deposition. The gas barrier laminate 10 can further improve its gas barrier properties by including the vapor-deposited layer 3. The vapor-deposited layer 3 is composed of an inorganic substance. Examples of the inorganic substance include metals and metal oxides.

[0063] As the metal constituting the metal or metal oxide, at least one metal selected from the group consisting of Si, Al, Mg, Sn, Ti and In can be listed. As the metal oxide, it is preferably selected from silicon oxide (SiO x ) and aluminum oxide (AlO x ) is at least one of the group consisting of SiO x and AlO x All of them have excellent water vapor barrier properties, and thus the water vapor barrier properties of the gas barrier laminate 10 can be improved. Among them, as the metal oxide, SiO x In this case, the gas barrier laminate 10 can have more excellent water vapor barrier properties.

[0064] The vapor-deposited layer 3 may be composed of a single layer or a plurality of layers.

[0065] The thickness of the vapor-deposited layer 3 is not particularly limited, but is preferably 5 nm or more. In this case, the gas barrier properties of the gas barrier laminate 10 are further improved compared to the case where the thickness of the vapor-deposited layer 3 is less than 5 nm. The thickness of the vapor-deposited layer 3 is more preferably 8 nm or more, and particularly preferably 10 nm or more.

[0066] In addition, the thickness of the vapor-deposited layer 3 is preferably 80 nm or less. In this case, the flexibility of the gas barrier laminate 10 is further improved compared to the case where the thickness of the vapor-deposited layer 3 exceeds 80 nm, and the gas barrier properties of the gas barrier laminate 10 after abuse can be further improved. In addition, the gas barrier properties of the gas barrier laminate 10 after high-temperature boiling treatment can be further improved. The thickness of the vapor-deposited layer 3 can be 70 nm or less, or 60 nm or less.

[0067] (Gas barrier coating layer)

[0068] The gas barrier coating layer 4 is a layer that covers the vapor-deposited layer 3 and has gas barrier properties, and is composed of a cured product of a composition for forming a gas barrier coating layer.

[0069] On the surface of the gas barrier coating layer 4, the ratio of silicon atoms to carbon atoms (hereinafter also referred to as "Si / C") measured by X-ray photoelectron spectroscopy (hereinafter also referred to as "XPS") is 0.25 to 0.90, and the peak half-value width of the Si2p orbital is 1.85 eV or less. In this case, compared with the case where Si / C exceeds 0.90, the gas barrier coating layer 4 becomes soft and less likely to break, and the gas barrier properties of the gas barrier laminate 10 after high-temperature retorting treatment can be further improved. In addition, compared with the case where Si / C is less than 0.25, the gas barrier coating layer 4 has stronger resistance to hot water, thereby further improving the gas barrier properties of the gas barrier laminate 10 after high-temperature retorting treatment.

[0070] In addition, the adhesion between the gas barrier coating layer 4 and the sealing layer of the gas barrier laminate 10 after high temperature retorting can be further improved compared to the case where the peak half width of the Si2p orbital exceeds 1.85 eV. The reason for this is not yet clear, but is presumed as follows.

[0071] That is, the peak that appears in the binding energy region of 100 to 107 eV in the narrow spectrum of the Si2p orbital is composed of a collection of various bonds (Si-O bonds, Si-OH bonds, Si-C bonds, etc.), and a large half-value width of the peak means that there are many types of bonds. When the half-value width is greater than 1.85 eV, the state is a state in which there are many unreacted Si-OH bonds and other bonds in addition to the Si-O bond. In contrast, when the half-value width is less than 1.85 eV, the state is a state in which there are not many unreacted Si-OH bonds and other bonds in addition to the Si-O bond. Therefore, in the gas barrier coating layer 4 in this state, the performance degradation caused by the high-temperature cooking treatment can be suppressed, especially the reduction in the adhesion between the gas barrier coating layer 4 and the sealing layer.

[0072] Regarding Si / C, narrow spectrum analysis was performed using the following measuring equipment and under the following measuring conditions to obtain narrow spectra of O1s, N1s, C1s, and Si2p orbitals on the surface of the gas barrier coating layer 4. For each element of O, N, C, and Si, relative sensitivity coefficients of 1.00 eV for C1s and 0.9 eV for Si2p were used, and element quantitative values ​​(atomic %) were obtained from their respective peak areas, and the obtained element quantitative values ​​were used for calculation. It should be noted that the ratio of silicon atoms to carbon atoms (Si / C) is an atomic number ratio.

[0073] <Measurement equipment>

[0074] JPS-9030 photoelectron spectrometer manufactured by JEOL Ltd.

[0075] <Measurement conditions>

[0076] (Spectrum sampling conditions)

[0077] Incident X-ray: MgKα (hν=1253.6eV)

[0078] X-ray output: 100W (10kV·10mA)

[0079] Measurement area: Circular area with a diameter of 6 mm

[0080] Photoelectron capture angle: 90°

[0081] (Measurement conditions)

[0082] Dwell Time: 100ms

[0083] Measurement step: 0.2eV

[0084] Channel energy: 10eV

[0085] Total times: 5 times

[0086] For the narrow spectra of O1s, N1s, C1s, and Si2p orbitals on the surface of the gas barrier coating layer 4 obtained as described above, the CC bond peak in the narrow spectrum of the C1s orbital is set to 285.0 eV for charge correction, and the peak half-value width of the Si2p orbital is calculated in the range of 100 to 107 eV of the narrow spectrum of the Si2p orbital after charge correction. The above-mentioned charge correction is performed by taking the difference between the obtained CC bond peak position and 285.0 eV as the peak shift, and shifting the energy position of all atoms by the peak shift amount.

[0087] The peak half-value width of the Si 2p orbital refers to the width of the peak when the value P of the number of photoelectrons on the vertical axis of the narrow spectrum of the Si 2p orbital is a value represented by the following formula (3).

[0088] P = 1 / 2 (A + B)…(3)

[0089] In the above formula (3), A represents the maximum value of the peak appearing in the binding energy region of 100 to 107 eV in the narrow spectrum of the Si2p orbital, and B represents the background value at the energy position corresponding to the maximum value of the above peak. Here, the background is obtained by the Shirley method with 100 eV and 107 eV as the two ends of the peak. Specifically, the peak half-value width of the Si2p orbital is obtained using the software SpecSurf Ver.2.0 attached to the above photoelectron spectrometer.

[0090] Si / C may be 0.90 or less, preferably 0.85 or less, more preferably 0.65 or less, further preferably 0.55 or less, and particularly preferably 0.45 or less. When Si / C is 0.85 or less, the gas barrier properties of the gas barrier laminate 10 after the high temperature retort treatment tend to be further improved. In addition, Si / C may be 0.25 or more, but from the viewpoint of improving the adhesion between the sealing layer and the gas barrier coating layer 4, it is preferably 0.30 or more, and more preferably 0.33 or more.

[0091] The peak half width of the Si2p orbital may be 1.85 eV or less, and is preferably 1.75 eV or less. When the peak half width of the Si2p orbital is 1.75 eV or less, the adhesion between the sealing layer and the gas barrier coating layer 4 tends to be further improved.

[0092] In addition, the peak half-value width of the Si 2p orbital can be, for example, 0.7 eV or more.

[0093] The composition for forming a gas barrier coating layer contains a water-soluble polymer, a first silicon compound, and a second silicon compound.

[0094] As water-soluble polymers, for example, polyvinyl alcohol resins, modified bodies thereof, and polyacrylic acid can be cited. They can be used alone or in combination of two or more. Among them, polyvinyl alcohol resins or modified bodies thereof are preferred as water-soluble polymers. In this case, the composition can impart better gas barrier properties to the gas barrier laminate 10 by curing. In addition, even if the composition is cured, it can impart better softness to the gas barrier laminate 10, and can further improve the gas barrier properties after abuse.

[0095] When the water-soluble polymer is composed of a polyvinyl alcohol resin or a modified product thereof, the saponification degree of the water-soluble polymer is not particularly limited, but is preferably 95% or more, and may be 100% from the viewpoint of improving the gas barrier properties of the gas barrier layered product 10 .

[0096] The degree of polymerization of the water-soluble polymer is not particularly limited, but is preferably 300 or more from the viewpoint of improving the gas barrier properties of the gas barrier laminate 10. The degree of polymerization of the water-soluble polymer is preferably 450 to 2,400.

[0097] The content of the water-soluble polymer in the solid component is not particularly limited, but is preferably 25% by mass or more. In this case, even after the gas barrier layered product 10 is subjected to a high-temperature retort treatment, the gas barrier properties can be further improved by curing.

[0098] The content of the water-soluble polymer in the solid component is preferably 30% by mass or more, more preferably 40% by mass or more, and particularly preferably 45% by mass or more. When the content of the water-soluble polymer in the solid component is 30% by mass or more, the gas barrier properties can be further improved by curing even after the gas barrier layered product 10 is subjected to a high-temperature retort treatment, compared to a case where the content of the water-soluble polymer in the solid component is less than 30% by mass.

[0099] The content of the water-soluble polymer in the solid component only needs to be less than 100% by mass, preferably 80% by mass or less, more preferably 70% by mass or less, and particularly preferably 60% by mass or less. When the content of the water-soluble polymer in the solid component is 80% by mass or less, the adhesion between the gas barrier coating layer 4 and the sealant layer of the gas barrier laminate 10 after high-temperature retorting can be further improved compared to the case where the content of the water-soluble polymer in the solid component exceeds 80% by mass.

[0100] The first silicon compound includes at least one of a silane alkoxy compound and a hydrolyzate thereof. The silane alkoxy compound is preferably represented by the following general formula (1). In this case, the adhesion between the gas barrier coating layer 4 and the vapor-deposited layer 3 can be improved, and delamination of the gas barrier laminate 10 can be suppressed.

[0101] Si(OR 1 )4······(1)

[0102] In the general formula (1), OR 1 represents a hydrolyzable group. 1 , alkyl and -C2H4OCH3 can be listed. As the alkyl, for example, methyl, ethyl, etc. can be listed. Among them, ethyl is preferred. In this case, the silane alkoxy compound is tetraethoxysilane (TEOS), which can be relatively stable in an aqueous solvent after hydrolysis.

[0103] The content of the first silicon compound in the solid component is not particularly limited, but is preferably 25% by mass or more, more preferably 30% by mass or more, and particularly preferably 40% by mass or more. In this case, compared with the case where the content of the first silicon compound in the solid component is less than 25% by mass, the gas barrier properties can be further improved by curing even after the gas barrier layered product 10 is subjected to a high-temperature retort treatment.

[0104] The content of the first silicon compound in the solid component is preferably 70% by mass or less, more preferably 60% by mass or less, and particularly preferably 50% by mass or less. In this case, compared with the case where the content of the first silicon compound in the solid component exceeds 70% by mass, the gas barrier properties can be further improved by curing even after the gas barrier layered product 10 is subjected to a high-temperature retort treatment.

[0105] The second silicon compound is a silane coupling agent as a curing agent, including at least one of a silane alkoxy compound and a hydrolyzate thereof. The silane alkoxy compound is preferably represented by the following general formula (2). In this case, the adhesion between the gas barrier coating layer 4 and the vapor-deposited layer 3 can be improved, and delamination between layers in the gas barrier laminate 10 can be suppressed.

[0106] (R 2 Si(OR 3 )3) n ······(2)

[0107] In the general formula (2), R 2 Represents a monovalent organic group, OR 3 represents a hydrolyzable group. n represents an integer of 1 or greater.

[0108] As R 2 The monovalent organic group represented may include a monovalent organic group containing a vinyl group, an epoxy group, a mercapto group, an amino group or an isocyanate group. Among them, the monovalent organic group is preferably an isocyanate group. In this case, the composition can have better hot water resistance by curing, and even after high-temperature boiling treatment, a greater lamination strength can be given to the gas barrier laminate 10.

[0109] As R 3 , alkyl and -C2H4OCH3 can be listed. As the alkyl, for example, methyl, ethyl, etc. can be listed. Among them, methyl is preferred. In this case, hydrolysis proceeds rapidly.

[0110] It should be noted that R 3 Can be used with R 2 The same may also be different. 3 They can be the same or different from each other.

[0111] n represents an integer greater than 1. When n is 1, the silane coupling agent represents a monomer, and when n is greater than 2, the silane coupling agent represents a polymer. n is preferably 3. In this case, the hot water resistance of the gas barrier coating layer 4 can be further improved, and a greater lamination strength can be imparted to the gas barrier laminate 10 even after high-temperature retorting.

[0112] As the second silicon compound (silane coupling agent), for example, silane coupling agents having a vinyl group such as vinyl trimethoxysilane and vinyl triethoxysilane; silane coupling agents having an epoxy group such as 3-glycidoxypropyl trimethoxysilane, 3-glycidoxypropyl triethoxysilane, 3-glycidoxypropyl methyl dimethoxysilane, and 3-glycidoxypropyl ethyl diethoxysilane; silane coupling agents having a mercapto group such as 3-mercaptopropyl trimethoxysilane and 3-mercaptopropyl methyl dimethoxysilane; silane coupling agents having an amino group such as 3-aminopropyl trimethoxysilane and 3-aminopropyl triethoxysilane; silane coupling agents having an isocyanate group such as 3-isocyanate propyl triethoxysilane and 1,3,5-tris (3-methoxysilyl propyl) isocyanurate. These silane coupling agents can be used alone or in combination of two or more.

[0113] The content of the second silicon compound in the solid component is not particularly limited, but is preferably 3% by mass or more, more preferably 5% by mass or more, and particularly preferably 7% by mass or more. In this case, compared with the case where the content of the second silicon compound in the solid component is less than 3% by mass, even after high-temperature retorting, the gas barrier laminate 10 can be cured to provide a greater lamination strength.

[0114] The content of the second silicon compound in the solid component is preferably 20% by mass or less, more preferably 15% by mass or less, and particularly preferably 12% by mass or less. In this case, compared with the case where the content of the second silicon compound in the solid component exceeds 20% by mass, the contents of the water-soluble polymer and the first silicon compound in the gas barrier coating layer 4 are relatively increased, so that good gas barrier properties can be maintained.

[0115] It should be noted that when calculating the content of the water-soluble polymer, the first silicon compound, and the second silicon compound in the solid component, when the first silicon compound contains at least one of the silane oxy compound represented by the general formula (1) and its hydrolyzate, the mass of the first silicon compound is converted to the mass of SiO2 for calculation, and when the second silicon compound contains at least one of the silane oxy compound represented by the general formula (2) and its hydrolyzate, the mass of the second silicon compound is converted to (R 2 Si(OH)3) n The mass is calculated.

[0116] (Other ingredients in solid content)

[0117] The solid content may further contain known additives such as a dispersant, a stabilizer, a viscosity modifier, and a colorant as necessary within a range that does not impair the gas barrier properties of the gas barrier coating layer 4 .

[0118] (Total content of components in solid content)

[0119] The total content of the water-soluble polymer, the first silicon compound and the second silicon compound (silane coupling agent) in the solid component is not particularly limited, but is usually 95% by mass or more, preferably 97% by mass or more, and may be 100% by mass.

[0120] (liquid)

[0121] As the liquid for dissolving or dispersing the above-mentioned solid components, an aqueous medium is generally used. As the aqueous medium, water, a hydrophilic organic solvent or a mixture thereof can be cited. As the hydrophilic organic solvent, for example, alcohols such as methanol, ethanol, and isopropanol; ketones such as acetone and methyl ethyl ketone; ethers such as tetrahydrofuran; cellosolves; carbitols; nitriles such as acetonitrile, etc. can be cited. These can be used alone or in combination of two or more.

[0122] The aqueous medium is preferably an aqueous medium consisting only of water or an aqueous medium containing water as a main component. When the aqueous medium contains water as a main component, the content of water in the aqueous medium is preferably 70% by mass or more, more preferably 80% by mass or more.

[0123] The thickness of the gas barrier coating layer 4 is not particularly limited, but is preferably 100 nm or more.

[0124] In this case, compared with the case where the thickness of the gas barrier coating layer 4 is less than 100 nm, the gas barrier properties can be further improved even after the gas barrier laminate 10 is subjected to a high-temperature retort treatment.

[0125] From the viewpoint of improving the gas barrier property, the thickness of the gas barrier coating layer 4 is more preferably 150 nm or more, particularly preferably 200 nm or more.

[0126] On the other hand, the thickness of the gas barrier coating layer 4 is preferably 700 nm or less. Compared with a case where the thickness of the gas barrier coating layer 4 exceeds 700 nm, the gas barrier laminate 10 is less likely to curl and can be easily used as a gas barrier laminate for a packaging film included in a packaging bag.

[0127] From the viewpoint of further improving the flexibility of the gas barrier laminate 10 , the thickness of the gas barrier coating layer 4 is more preferably 500 nm or less, particularly preferably 400 nm or less.

[0128] <Method for producing gas barrier laminate>

[0129] Next, a method for producing the gas barrier laminate 10 will be described.

[0130] First, the base material layer 1 is prepared.

[0131] Next, the anchor coating layer 2 is formed on one surface of the base material layer 1 .

[0132] Specifically, the anchor coating layer 2 is formed by applying the anchor coating layer forming composition to one surface of the base layer 1 and heating and drying it. The heating temperature is, for example, 50 to 200° C. and the drying time is, for example, about 10 seconds to 10 minutes.

[0133] Next, the vapor-deposited layer 3 is formed on the anchor coating layer 2 .

[0134] The vapor deposition layer 3 can be formed, for example, by a vacuum film-forming method. As vacuum film-forming methods, physical vapor deposition and chemical vapor deposition can be listed. As physical vapor deposition methods, vacuum evaporation, sputtering evaporation, ion plating, etc. can be listed. As physical vapor deposition methods, vacuum evaporation is particularly preferably used. As vacuum evaporation methods, resistance heating vacuum evaporation, EB (electron beam) heating vacuum evaporation, and induction heating vacuum evaporation can be listed. As chemical vapor deposition methods, thermal CVD, plasma CVD, and optical CVD can be listed.

[0135] Next, a gas barrier coating layer 4 is formed on the vapor-deposited layer 3. The gas barrier coating layer 4 is formed in such a manner that, when the surface of the gas barrier coating layer 4 is subjected to elemental quantitative analysis using X-ray photoelectron spectroscopy, the ratio of silicon atoms to carbon atoms (Si / C) is 0.25 to 0.90, and the peak half-value width of the narrow spectrum of the Si2p orbital appearing at 100 to 107 eV is 1.85 eV or less.

[0136] The gas barrier coating layer 4 can be formed, for example, by applying and curing a composition for forming a gas barrier coating layer on the deposited layer 3. Here, curing the solid component means that the water-soluble polymer, the first silicon compound and the second silicon compound in the solid component react with each other and become integrated.

[0137] As a coating method for the gas barrier coating layer-forming composition, a known method can be adopted, and specific examples of the coating method include wet film-forming methods such as gravure coating, dip coating, reverse coating, wire bar coating, and die coating.

[0138] Curing can be performed by, for example, heating or the like.

[0139] When curing is performed by heating, the gas barrier coating layer 4 may be heated at a temperature of, for example, 65 to 130° C. and for a heating time of 5 seconds to 2 minutes while adjusting the mass ratio of PVA, TEOS, and SC agent.

[0140] As described above, the gas barrier laminate 10 is obtained.

[0141] <Packaging film>

[0142] Next, refer to Figure 2 The embodiments of the packaging film disclosed in the present invention are described. Figure 2 In, with Figure 1 The same components are denoted by the same reference numerals, and repeated descriptions are omitted.

[0143] Figure 2 is a cross-sectional view showing an embodiment of the packaging film of the present disclosure. Figure 2 As shown, the packaging film 20 includes a gas barrier laminate 10 and a sealant layer 21 laminated on the gas barrier laminate 10, and the sealant layer 21 is arranged on the gas barrier coating layer 4 side of the base layer 1 of the gas barrier laminate 10. Figure 2 As shown, in the gas barrier laminate 10 , the gas barrier coating layer 4 and the sealant layer 21 may be bonded together via the adhesive layer 22 , or the gas barrier coating layer 4 and the sealant layer 21 may be directly bonded together.

[0144] Since the packaging film 20 includes the gas barrier laminate 10 , it has excellent gas barrier properties even after high-temperature retorting, and can suppress peeling between the sealant layer 21 and the gas barrier coating layer 4 in the gas barrier laminate 10 constituting the packaging film 20 .

[0145] As the material of the adhesive layer 22, polyester-isocyanate resin, urethane resin, polyether resin, etc. can be used. When the packaging film 20 is used for retort application, a two-component curing type urethane adhesive having retort resistance can be preferably used.

[0146] (Sealing layer)

[0147] As the material of the sealing layer 21, thermoplastic resins such as polyolefin resins and polyester resins can be listed, and polyolefin resins are generally used. Specifically, as the polyolefin resin, ethylene resins such as low-density polyethylene resin (LDPE), medium-density polyethylene resin (MDPE), linear low-density polyethylene resin (LLDPE), ethylene-vinyl acetate copolymer (EVA), ethylene-α-olefin copolymer, ethylene-(meth)acrylic acid copolymer, etc.; polypropylene resins such as homopolypropylene (PP), propylene-ethylene random copolymer, propylene-ethylene block copolymer, propylene-α-olefin copolymer, etc.; or mixtures thereof can be used. The material of the sealing layer 21 can be appropriately selected from the above-mentioned thermoplastic resins according to the use purpose, boiling treatment, high-temperature cooking treatment and other temperature conditions. In the case where the base material layer 1 contains a polyolefin resin, from the viewpoint of recyclability, the material of the sealing layer 21 is preferably a polyolefin resin. In addition, in the case where the base material layer 1 contains a polyester resin, from the viewpoint of recyclability, the material of the sealing layer 21 is preferably a polyester resin.

[0148] The thermoplastic resin constituting the sealant layer 21 may be stretched or not stretched, but is preferably not stretched from the viewpoint of lowering the melting point and facilitating heat sealing.

[0149] The thickness of the sealant layer 21 is appropriately determined according to the mass of the content, the shape of the packaging bag, etc., and is not particularly limited. From the viewpoint of the flexibility and adhesiveness of the packaging film 20, the thickness is preferably 30 to 150 μm.

[0150] <Packaging products>

[0151] Next, refer to Figure 3 The embodiments of the packaging product disclosed in the present invention are described. It should be noted that: Figure 3 is a side view showing one embodiment of the packaging product of the present disclosure. Figure 3 In, with Figure 1 or Figure 2 The same components are denoted by the same reference numerals, and repeated descriptions are omitted.

[0152] like Figure 3 As shown, the packaged product 40 includes a packaging container 30 and content C filled in the packaging container 30 . Figure 3 The packaging container 30 shown is obtained by using a pair of packaging films 20 and heat-sealing the peripheral edges of the packaging films 20 in a state where the sealing layers 21 face each other. Figure 3 In the figure, the adhesive layer 22 of the packaging film 20 is omitted.

[0153] The packaging product 40 includes a packaging container 30, which has excellent gas barrier properties even after high-temperature cooking treatment, and can inhibit the peeling between the gas barrier coating layer 4 and the sealing layer 21 contained in the gas barrier laminate in the packaging film 20, thereby inhibiting the quality reduction of the content C caused by the mixing of oxygen for a long time.

[0154] In addition, the packaging container 30 can also be obtained by bending one packaging film 20 and heat-sealing the peripheral edge portion of the packaging film 20 in a state where the sealing layers 21 face each other.

[0155] Examples of the packaging container 30 include packaging bags, laminated tube containers, and liquid paper containers.

[0156] The content C is not particularly limited, and examples of the content C include food, liquid, medicine, and electronic components.

[0157] It should be noted that the gist of the present disclosure is as follows.

[0158] [1] A gas barrier laminate comprising, in this order, a base layer comprising a thermoplastic resin, a vapor deposited layer, and a gas barrier coating layer,

[0159] When the surface of the gas barrier coating layer is subjected to elemental quantitative analysis using X-ray photoelectron spectroscopy, the ratio of silicon atoms to carbon atoms (Si / C) is 0.25 to 0.90, and the peak half-value width of the narrow spectrum of Si2p orbitals appearing at 100 to 107 eV is less than 1.85 eV.

[0160] [2] The gas barrier laminate according to [1], wherein the thermoplastic resin is polypropylene.

[0161] [3] The gas barrier laminate according to [1] or [2], further comprising an anchor coating layer between the substrate layer and the vapor-deposited layer.

[0162] [4] The gas barrier laminate according to any one of [1] to [3], wherein the gas barrier coating layer is composed of a cured product of a composition containing at least one silicon compound and a water-soluble polymer, wherein the at least one silicon compound is selected from the group consisting of a silane alkoxy compound represented by the following general formula (1), a hydrolyzate of a silane alkoxy compound represented by the following general formula (1), a silane alkoxy compound represented by the following general formula (2), and a hydrolyzate of a silane alkoxy compound represented by the following general formula (2);

[0163] Si(OR 1 )4······(1)

[0164] (In the general formula (1), OR 1represents a hydrolyzable group. )

[0165] (R 2 Si(OR 3 )3) n ······(2)

[0166] (In the general formula (2), R 2 Represents a monovalent organic group, OR 3 represents a hydrolyzable group. n represents an integer greater than 1.)

[0167] [5] The gas barrier laminate according to any one of [1] to [4], wherein the gas barrier coating layer is composed of a cured product of a composition containing a water-soluble polymer, a first silicon compound, and a second silicon compound,

[0168] The first silicon compound contains at least one of a silane alkoxy compound represented by the following general formula (1) and a hydrolyzate thereof,

[0169] The second silicon compound contains at least one of a silane alkoxy compound represented by the following general formula (2) and a hydrolyzate thereof,

[0170] Si(OR 1 )4······(1)

[0171] (In the general formula (1), OR 1 represents a hydrolyzable group. )

[0172] (R 2 Si(OR 3 )3) n ······(2)

[0173] (In the general formula (2), R 2 Represents a monovalent organic group, OR 3 represents a hydrolyzable group. n represents an integer greater than 1.)

[0174] [6] The gas barrier laminate according to any one of [1] to [5], wherein the thickness of the gas barrier coating layer is from 100 nm to 700 nm.

[0175] [7] The gas barrier laminate according to [4] or [5], wherein the water-soluble polymer of the gas barrier coating layer is a polyvinyl alcohol resin or a modified product thereof.

[0176] [8] The gas barrier laminate according to any one of [1] to [7], wherein the vapor-deposited layer contains at least one selected from aluminum oxide and silicon oxide.

[0177] [9] A packaging film comprising the gas barrier laminate according to any one of [1] to [8], and a sealant layer.

[0178]

[10] A packaging container comprising the packaging film described in [9].

[0179]

[11] A packaged product comprising the packaging container according to

[10] and a content filled in the packaging container.

[0180] Example

[0181] Hereinafter, the present disclosure will be specifically described with reference to examples, but the present disclosure is not limited to these examples.

[0182] <Preparation of coating solution>

[0183] Coating liquids A to C of the gas barrier coating layer-forming compositions used in Examples and Comparative Examples were prepared as follows.

[0184] (Coating liquid A)

[0185] Solution A: A 5 mass % aqueous solution of polyvinyl alcohol (PVA, trade name: Kuraray POVAL 60-98, manufactured by Kuraray Co., Ltd.) which is a water-soluble polymer.

[0186] (Coating liquid B)

[0187] A solution obtained by mixing tetraethoxysilane (TEOS, trade name: KBE04, solid content: 100%, manufactured by Shin-Etsu Chemical Co., Ltd.) as a silane oxide compound or a first silane oxide compound, methanol (manufactured by Kanto Chemical Co., Ltd.) and 0.1N hydrochloric acid (manufactured by Kanto Chemical Co., Ltd.) at a mass ratio of 17 / 10 / 73 and hydrolyzing them (TEOS hydrolyzed solution)

[0188] (Coating liquid C)

[0189] A silane coupling agent (hereinafter referred to as "SC agent") or 1,3,5-tris(3-methoxysilylpropyl)isocyanurate (SC) as the second siloxy compound was added to a mixed solution of water / IPA=1 / 1 in a mass ratio so that the solid content ratio was 5 mass % (converted to (R 2 Si(OH)3) n . R 2 The solution is diluted and adjusted in the manner of -(CH2)3NC=O-, where n is 3.

[0190] <Preparation of Anchor Coat Layer-Forming Composition>

[0191] The AC1 layer-forming composition and the AC2 layer-forming composition as the anchor coating layer-forming composition used in Examples or Comparative Examples were prepared as follows.

[0192] (AC1 layer forming composition)

[0193] The AC1 layer-forming composition, which is an anchor coat layer-forming composition, was prepared as follows.

[0194] Acrylic polyol and toluene diisocyanate were mixed so that the number of NCO groups of toluene diisocyanate was equal to the number of OH groups of acrylic polyol, and diluted with ethyl acetate so that the total solid content (the total amount of acrylic polyol and toluene diisocyanate) was 5% by mass. β-(3,4-epoxycyclohexyl)trimethoxysilane was further added to the diluted mixed solution so that it was 5 parts by mass relative to 100 parts by mass of the total amount of acrylic polyol and toluene diisocyanate, and these were mixed to prepare a composition for forming an anchor coating layer (anchor coating agent).

[0195] (AC2 layer forming composition)

[0196] The AC2 layer-forming composition as the anchor coating layer-forming composition was prepared as follows: That is, the AC2 layer-forming composition was prepared by mixing Takelac WPB-341 (manufactured by Mitsui Chemicals, Inc.) and isocyanate silane KBE-403 (manufactured by Shin-Etsu Chemical Co., Ltd.) at a solid content ratio of 9:1.

[0197] <Production of Gas Barrier Laminate>

[0198] (Example 1)

[0199] A gas barrier laminate was produced in a roll-to-roll manner as follows: First, a 20 μm thick polypropylene film (product name “ME-1”, manufactured by Mitsui Chemicals Tohcello, Inc.) was mounted on an unwinding device, a conveying device, and a winding device as a substrate layer.

[0200] Next, the substrate layer was released, and an anchor coating layer-forming composition AC1 was applied to the substrate layer being conveyed so as to have a film thickness of 120 nm, followed by drying at 90° C. for 5 seconds to form an anchor coating layer 1 (AC1 layer) as an intermediate layer.

[0201] Next, SiO was formed on the AC1 layer to a thickness of 25 nm. x At this time, SiO xThe film was formed by using a vacuum evaporation device using electron beam heating to evaporate the silicon ingot at a pressure of 1×10 -2 Pa to introduce oxygen.

[0202] Next, three solutions, coating solution A, coating solution B, and coating solution C, were mixed to prepare a coating solution. The coating solution was adjusted so that the solid components of PVA, TEOS (SiO2 conversion value), and SC agent (R 2 Si(OH)3) n The coating solution was applied on the vapor deposited layer by gravure coating so that the thickness after drying became the value shown in Table 1, and heated at the heating temperature shown in Table 1 for 1 minute to form a gas barrier coating layer.

[0203] As described above, a gas barrier laminate in which the base material layer, the vapor-deposited layer, and the gas barrier coating layer are sequentially laminated is obtained.

[0204] The gas barrier laminate thus obtained was subjected to narrow spectrum analysis using the following measuring equipment and under the following measuring conditions to obtain narrow spectra of O1s, N1s, C1s, and Si2p orbitals on the surface of the gas barrier coating layer.

[0205] Then, for each element of O, N, C and Si, the relative sensitivity coefficients of O1s of 2.28 eV, N1s of 1.61 eV, C1s of 1.00 eV, and Si2p of 0.9 eV were used to obtain the element quantitative value (atomic %) from the respective peak areas, and Si / C was calculated using the obtained element quantitative value. The results are shown in Table 1.

[0206] Next, the CC bond peak in the narrow spectrum of the C1s orbital was set to 285.0 eV, and the charge correction of each narrow spectrum was performed.

[0207] Furthermore, the half-value width of the peak of Si2p orbital (the half-value width of the peak appearing in the binding energy region of 100 to 107 eV in the narrow spectrum of Si2p orbital) was determined using SpecSurf Ver.2.0 software included in the photoelectron spectrometer. The results are shown in Table 1.

[0208] <Measurement equipment>

[0209] JPS-9030 photoelectron spectrometer manufactured by JEOL Ltd.

[0210] <Measurement conditions>

[0211] (Spectrum sampling conditions)

[0212] Incident X-ray: MgKα (hν=1253.6eV)

[0213] X-ray output: 100W (10kV·10mA)

[0214] Measurement area: Circular area with a diameter of 6 mm

[0215] Photoelectron capture angle: 90°

[0216] (Measurement conditions)

[0217] Dwell Time: 100ms

[0218] Measurement step: 0.2eV

[0219] Channel energy: 10eV

[0220] Total times: 5 times

[0221] (Examples 2 to 7 and Comparative Examples 1 to 3)

[0222] When preparing a coating liquid to form a gas barrier coating layer, PVA, TEOS (SiO2 conversion value) and SC agent ((R 2 Si(OH)3) n A gas barrier laminate was produced in the same manner as in Example 1 except that the mass ratio (mass %) of the gas barrier layer (converted value), the heating temperature, and the thickness of the gas barrier coating layer were set to the values ​​shown in Table 1.

[0223] For the gas barrier laminate thus obtained, Si / C was calculated and the peak half value width of Si2p orbital was determined in the same manner as in Example 1. The results are shown in Table 1.

[0224] (Example 8)

[0225] When forming the anchor coating layer as the intermediate layer, the AC2 layer forming composition was used as the anchor coating layer forming composition, and the AC2 layer was formed so as to have a film thickness of 1500 nm. When preparing the coating solution to form the gas barrier coating layer, the PVA, TEOS (SiO2 conversion value) and SC agent ((R 2 Si(OH)3) n A gas barrier laminate was produced in the same manner as in Example 1 except that the mass ratio (mass %) of the components (converted value) was set to the value shown in Table 1.

[0226] For the gas barrier laminate thus obtained, Si / C was calculated and the peak half value width of Si2p orbital was determined in the same manner as in Example 1. The results are shown in Table 1.

[0227] (Example 9)

[0228] When forming the vapor-deposited layer, the type and thickness of the vapor-deposited layer were set as shown in Table 1. When preparing the coating solution to form the gas barrier coating layer, the solid components of PVA, TEOS (SiO2 conversion value) and SC agent ((R 2 Si(OH)3) n A gas barrier laminate was produced in the same manner as in Example 1 except that the mass ratio (mass %) of the components (converted value) was set to the value shown in Table 1.

[0229] For the gas barrier laminate thus obtained, Si / C was calculated and the peak half value width of Si2p orbital was determined in the same manner as in Example 1. The results are shown in Table 1.

[0230] (Example 10)

[0231] Instead of forming an anchor coating layer as an intermediate layer on the substrate layer, the surface of the substrate layer is modified by reactive ion etching (RIE) to form an RIE layer as an intermediate layer. When preparing a coating liquid to form a gas barrier coating layer, PVA, TEOS (SiO2 conversion value) and SC agent ((R 2 Si(OH)3) n A gas barrier laminate was produced in the same manner as in Example 1 except that the mass ratio (mass %) of the components (converted value) was set to the value shown in Table 1.

[0232] For the gas barrier laminate thus obtained, Si / C was calculated and the peak half value width of Si2p orbital was determined in the same manner as in Example 1. The results are shown in Table 1.

[0233] [Production of laminated film]

[0234] A 60 μm thick unstretched polypropylene film (trade name "Torayfan ZK207", manufactured by Toray Industries, Ltd.) was adhered to the gas barrier coating layer side of the gas barrier laminate produced in the examples and comparative examples by a dry lamination method using a two-component curable urethane adhesive (trade name "A525 / A52") to produce a laminated film having a two-layer structure.

[0235] [evaluate]

[0236] (High temperature cooking treatment)

[0237] A packaging film having a size of 315 mm in length and 230 mm in width was cut from the laminated film prepared as described above and folded in half, and three sides were heat-sealed to prepare a bag having an opening. Water was put into the bag, and the opening was heat-sealed to prepare a sealed bag. The obtained sealed bag was subjected to a high-temperature retort treatment at 130°C for 60 minutes using a hot water storage retort.

[0238] (Gas Barrier Properties)

[0239] In order to evaluate the gas barrier properties of the laminated film after the high temperature retort treatment, the oxygen permeability was measured. An oxygen permeability measuring device (Modern Control, OXTRAN 2 / 20) was used to measure the gas barrier properties of the laminated film over a measurement area of ​​50 cm. 2 The measurement was carried out under the conditions of 30°C, 70% relative humidity. The measurement method was based on JIS K-7126, B method (isobaric method) and ASTM D3985-81. The measured value was expressed in units of [cc / m 2 ·day·atm] The results are shown in Table 1. It should be noted that if the oxygen permeability is 5.0cc / m 2 ·day·atm or less, the laminate film is judged to have excellent gas barrier properties.

[0240] (Adhesion)

[0241] In order to evaluate the adhesion between the gas barrier laminate and the sealing layer in the laminated film after high temperature boiling treatment, the lamination strength between the gas barrier coating layer and the unstretched polypropylene film was measured after removing the water. The measurement was carried out according to JIS K6854 with a test width of 15 mm, a peeling speed of 300 mm / min, and a peeling angle of T type. The measured value is expressed in units of [N / 15 mm]. The results are shown in Table 1. It should be noted that if the lamination strength is 2.0 N / 15 mm or more, it is judged that the gas barrier laminate and the sealing layer in the laminated film have excellent adhesion.

[0242] [Table 1]

[0243]

[0244] From the results shown in Table 1, it is understood that the gas barrier layered products of Examples 1 to 10 have excellent gas barrier properties even after high-temperature retorting treatment, and also have excellent adhesion to the sealant layer.

[0245] From the above, it was confirmed that the gas barrier laminate of the present disclosure has excellent gas barrier properties even after high-temperature retort treatment and has excellent adhesion with the sealant layer.

[0246] Explanation of symbols

[0247] 1 ...substrate layer, 3 ...evaporated layer, 4 ...gas barrier coating layer, 10 ...gas barrier laminate, 20 ...packaging film, 21 ...sealing layer, 30 ...packaging container, 40 ...packaging product.

Claims

1. A gas barrier laminate comprising, in order, a base layer comprising a thermoplastic resin, a vapor deposited layer, and a gas barrier coating layer, On the surface of the gas barrier coating layer, when the element quantitative analysis of the surface of the gas barrier coating layer is performed using X-ray photoelectron spectroscopy, the ratio of silicon atoms to carbon atoms Si / C is 0.25 to 0.90, and the half-value width of the peak appearing in the binding energy region of 100 to 107 eV in the narrow spectrum of the Si2p orbital is less than 1.85 eV. 2 . The gas barrier laminate according to claim 1 , wherein the thermoplastic resin is polypropylene. 3 . The gas barrier laminate according to claim 1 , further comprising an anchor coating layer between the base layer and the vapor-deposited layer.

4. The gas barrier laminate according to claim 1, wherein the gas barrier coating layer is composed of a cured product of a composition containing a water-soluble polymer, a first silicon compound and a second silicon compound, The first silicon compound contains at least one of a silane alkoxy compound represented by the following general formula (1) and a hydrolyzate thereof, The second silicon compound contains at least one of a silane alkoxy compound represented by the following general formula (2) and a hydrolyzate thereof, Si(OR 1 )4······(1) In the general formula (1), OR 1 represents a hydrolyzable group, (R 2 Si(OR 3 )3) n ······(2) In the general formula (2), R 2 Represents a monovalent organic group, OR 3 represents a hydrolyzable group, and n represents an integer of 1 or greater. The gas barrier laminate according to claim 1 , wherein the gas barrier coating layer has a thickness of 100 nm to 700 nm. 6 . The gas barrier laminate according to claim 4 , wherein the water-soluble polymer of the gas barrier coating layer is a polyvinyl alcohol resin or a modified product thereof. 7 . The gas barrier laminate according to claim 1 , wherein the vapor-deposited layer comprises at least one selected from the group consisting of aluminum oxide and silicon oxide. 8 . A packaging film comprising the gas barrier laminate according to claim 1 , and a sealant layer.

9. A packaging container comprising the packaging film according to claim 8. 10 . A packaged product comprising the packaging container according to claim 9 and a content filled in the packaging container.

Citation Information

Patent Citations

  • Gas barrier laminate and packaging bag

    WO2021220977A1

  • Gas barrier film

    CN105934338A

  • Laminated body and packaging bag

    CN114126974A

  • Barrier laminated film and retort food packaging body

    JP2018001630A

  • Barrier laminated film and food packaging body

    JP2018001631A